Dead metaphors and responsibilised bodies-in-transition: the implications of medical metaphors for understanding the consumption of preventative healthcare. Issue 5 (24th March 2022) - Cheded, Mohammed; Liu, Chihling; Hopkinson, Gillian
ABSTRACT: This paper argues that metaphorical formulations around genetic categories have important implications for individuals' experiences of their at-genetic-risk bodies vis-à-vis the market for prevention. Drawing on Jacques Derrida's concept of usure, our findings unpack three central biomedical metaphors that shape the ways in which 'previvor' women with the BRCA gene mutation manage and experience their (risky) body-in-transition against the market for prevention. These are the metaphors of: the container, the omnipresent danger, and battle and journey. Our discussion unravels the processes of the de/re-stabilisation of the (risky) body-in-transition, as well as the reconfiguration of individuals' rights and duties in the market for prevention to become a good genetic citizen. Moving beyond a discussion of 'consumer sovereignty', we contribute to developing a contextually nuanced understanding of the complex relations between the lived experiences of 'losing control' and the consumption of prevention.